Specific hunger- and satiety-induced tuning of guinea pig enteric nerve activity - Roosen, Lina (Blackwell Science Inc, 2012)
Although hunger and satiety are mainly centrally regulated, there is convincing evidence that also gastrointestinal motor activity and hormone fluctuations significantly contribute to appetite signalling. In this study, we investigated how motility and enteric nerve activity are set by fasting and feeding. By means of video-imaging, we tested whether peristaltic activity differs in ex vivo preparations from fasted and re-fed guinea pigs. Ca(2+) imaging was used to investigate whether the feeding state directly alters neuronal activity, either occurring spontaneously or evoked by (an)orexigenic signalling molecules. We found that pressure-induced (2 cmH(2)O) peristaltic activity occurs at a higher frequency in ileal segments from re-fed animals (re-fed versus fasted, 6.12 ± 0.22 vs. 4.84 ± 0.52 waves min(−1), P = 0.028), even in vitro hours after death. Myenteric neuronal responses were tuned to the feeding status, since neurons in tissues from re-fed animals remained hyper-responsive to high K(+)-evoked depolarization (P < 0.001) and anorexigenic molecules (P < 0.001), while being less responsive to orexigenic ghrelin (P = 0.013). This illustrates that the feeding status remains ‘imprinted’ex vivo. We were able to reproduce this feeding state-related memory in vitro and found humoral feeding state-related factors to be implicated. Although the molecular link with hyperactivity is not entirely elucidated yet, glucose-dependent pathways are clearly involved in tuning neuronal excitability. We conclude that a bistable memory system that tunes neuronal responses to fasting and re-feeding is present in the enteric nervous system, increasing responses to depolarization and anorexigenic molecules in the re-fed state, while decreasing responses to orexigenic ghrelin. Unlike the hypothalamus, where specific cell populations sensitive to either orexigenic or anorexigenic molecules exist, the enteric feeding state-related memory system is present at the functional level of receptor signalling rather than confined to specific neuron subtypes.